Fauna of metazoan parasites of Pterygoplichthys pardalis (Castelnau, 1855) sold at fairs in the city of Manaus, state of Amazonas, Brazil (Acta Scientiarum. Biological Sciences, 2023)
Pterygoplichthys pardalis is an endemic as well as economically important fish species in the Amazon basin. Thirty P. pardalis specimens were purchased at assorted fairs in the city of Manaus. Fish were necropsied, and then, had their organs investigated for parasites. The identified parasites were observed under Light bright field microscopy and that of Scanning Electron Microscopy (SEM). Through the analyses it was observed 219 metazoan parasite specimens, belonging to four taxonomic groups: Monogenoidea, Digenea, Acanthocephala, and Copepoda. Six metazoan parasitic species were identified: Monogenoidea Unilatus unilatus Mizelle and Kritsky, 1967 and Copepoda Therodamas elongatus (Thatcher, 1986) from the gills, Digenea Austrodiplostomum compactum (Lutz, 1928), Megacoelium spinicavum Szidat, 1954 and Diplostomum sp. from the eyes, stomach, and gonads, respectively, and Acanthocephala Gorytocephalus elongorchis Thatcher, 1979 from the intestine. Gorytocephalus elongorchis was the one presenting the highest prevalence value, followed by digeneans M. spinicavum, Diplostomum sp., and A. compactum. The present study has come to provide the very first SEM M. spinicavum, G. elongorchis, and T. elongatus images, thus improving on the up to now available data addressing P. pardalis parasitic fauna, which has been found to be infecting, the fish species presently being marketed in Manaus. Moreover, the current survey has demonstrated the identified parasite species pose no public health concern at all.